MEMBEDAH PRINSIP PELAPORAN KONSERVATISME AKUNTANSI: PRO KONTRA, KEGUNAAN DAN PERTIMBANGAN UNTUK PEMANGKU KEPENTINGAN - I Made Dwi Hita Darmawan (Politeknik Negeri Ambon, 2023)
The pros and cons of corporate reporting with the principle of accounting conservatism are increasingly becoming a hot topic of discourse from time to time. The purpose of this research is as a clear guideliness for users of financial statements such as investors, financial analysts to stakeholders because often companies use this method by setting the company's profit scenario to be low in the initial period so that there will be hidden reserves. Descriptive qualitative method through literature study is used to explore and analyze empirical studies related to accounting conservatism fully and deeply. The results found that so far there have been pros and cons of the principle of accounting conservatism which has a strong argumentative level on each side. Supporters of this principle emphasize the usefulness of parsing conflicts of interest from managers who will tend to increase profits to attract investors, while the con side considers that this principle creates unrecorded reserves, allowing management to more freely report future profit figures which will cause conflicts of interest. This study also found that earnings management and accounting conservatism are closely related. Basically, earnings management is present to manipulate the available alternatives and take the best decision to be able to achieve the projected profit level. As a result, management can play a low profit now, then a larger profit in the future period, so that management receives a bonus.